HUBUNGAN USIA DAN JARAK KEHAMILAN DENGAN KEJADIAN KETUBAN PECAH DINI DI RUMAH SAKIT UMUM DAERAH KOTA KENDARI - Saida, Saida; Rachmad, Alda Ayu Syakila (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Premature rupture of membranes (PROM) refers to the rupture of membranes before the onset of labor. PROM is a serious problem in obstetrics. The incidence of PROM worldwide ranges from 5% to 10%. In addition, various risk factors can also cause PROM such as gestational age, gestational distance, fetal abnormality and multiple pregnancies. The purpose of this study was to analyze the factors associated with the incidence of premature rupture of membranes in laboring mothers at Kendari City Regional General Hospital. This study is an observational analytic study with a cross-sectional design. Data were obtained by observing medical records. The sample of this study were pregnant women who entered the delivery room of Kendari City Hospital in 2022. The sampling technique used simple random sampling technique. The dependent variable in this study was premature rupture of membranes and the independent variables were gestational age, gestational distance, fetal abnormality and multiple pregnancy. Data were analyzed by Chi-square test. The results of the analysis showed that there was a relationship between gestational age (p = 0.038) gestational distance (p = 0.001). There is a significant relationship between gestational age, gestational distance and fetal abnormality with the incidence of premature rupture of membranes, and there is no significant relationship between multiple pregnancies and the incidence of premature rupture of membranes in laboring mothers at Kendari City Regional General Hospital.